Iron speciation in soda-lime-silica glass: a comparison of XANES and UV-vis-NIR spectroscopy1. Issue 7 (24th July 2015) - Ceglia, Andrea; Nuyts, Gert; Meulebroeck, Wendy; Cagno, Simone; Silvestri, Alberta; Zoleo, Alfonso; Nys, Karin; Janssens, Koen; Thienpont, Hugo; Terryn, Herman
<x xml:space="preserve">Abstract</x> XANES and UV-vis-NIR have been applied and compared for the determination Fe2+ in ancient glass.